2016
DOI: 10.4103/2231-0762.186790
|View full text |Cite
|
Sign up to set email alerts
|

Energy dispersive X-ray microanalysis, fluoride release, and antimicrobial properties of glass ionomer cements indicated for atraumatic restorative treatment

Abstract: Aim:The aim of this study was to compare constituents of glass powder, fluoride release, and antimicrobial properties of new atraumatic restorative treatment material with zirconia fillers and conventional glass ionomer cement (GIC) type IX.Materials and Methods:Thisin vitro study comparing Zirconomer and Fuji IX was executed in three parts: (1) energy dispersive X-ray microanalysis of glass powders (2) analysis of fluoride release at 1st, 3rd, 7th, 15th, and 30th day, and (3) antimicrobial activity against St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…13 In this study, the initial fluoride release of GCP Glass Fill, Amalgomer CR, Zirconomer, and Fuji IX materials occurred as a burst effect, in accordance with previous studies. 13,14,15,16,28 The highest fluoride release values were observed from Zirconomer in the Non-IR and IR subgroups on the first day, which may be attributed to its chemical composition as found in previous studies. 15,17 The fluoride release may provide antibacterial property to the restorative materials.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…13 In this study, the initial fluoride release of GCP Glass Fill, Amalgomer CR, Zirconomer, and Fuji IX materials occurred as a burst effect, in accordance with previous studies. 13,14,15,16,28 The highest fluoride release values were observed from Zirconomer in the Non-IR and IR subgroups on the first day, which may be attributed to its chemical composition as found in previous studies. 15,17 The fluoride release may provide antibacterial property to the restorative materials.…”
Section: Discussionsupporting
confidence: 69%
“…The use of fluoride-releasing restorative materials has gradually increased because of the inhibitory effects of fluoride on caries 5,11,13 while several laboratory studies have been also performed to evaluate the amount of fluoride release from the materials. 13,14,15,16,27 It has been reported that the higher fluoride release of GICs could provide higher antibacterial activity. 15,17 The fluoride release of restorative materials differs based on various factors such as material type, chemical composition, powder-liquid ratio used during material preparation, mixing method, surface area of material exposed to the environment, storage medium, pH of the environment or storage medium, surface treatment, and finishing procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations